The Influence of Physical Activity on Academic Performance Among Students-Athletes: A Case in a Secondary Public School (ACPES (ASEAN Council of Physical Education and Sport) in cooperation with Universitas Negeri Semarang (UNNES), 2023)
It is a common expectation that bookworm students can perform well and contribute more towards enhancement in academic performance instead of physically active student or best known as sport students. Thus, this study seeks to measure the level of physical activity and explore academic achievement, as well as to examine if there is a relationship between physically active students and academic achievement among student-athletes in a public secondary school in Kedah. Survey method was employed using a set of questionnaires. Purposive sampling method was used to gather information from 22 selected students-athletes involving 8 classes from various sports backgrounds. Results indicated that the associations of physical activity and fitness with cognitive function are relatively few but generally showed a positive association between physical activity and cognitive function of students.